(3GdCfeGW GdESJgdGcjI hGdEONGQjI aj GdeLJeY GdHOhj (B:s (3OQGSI aj GdCfJQhHhdhLjG GdEbJUGOjI (B/s - (3OYHS, eMeO jSQj GHQGgjes ((3GdEScfOQjI(B: s (3OGQ GdeYGQa(B, s, 1996)
(3CfeGW GdJHGOd aj GdeLJeY GdHOhj(B- (3GdCfeGW GdESJgdGcjI hGdEONGQjI aj GdeLJeY GdHOhj(B- (3GdJQGce hGdEgOGQ ddWGbI hddehGO aj GdeLJeY GdHOhjs
Keywords: (3GdEONGQs; (3GdJHGOds; (3Yde GdGLJeGY GdGbJUGOj, GdJLGQIs